Bragg wavelength detection based on zero phase filter - Yeow, Spencer Chang Fei. (2010)
Optic fibre Bragg grating (FBG) is very useful in optic fibre sensing. It can reflect particular wavelength which is sensitive to target physical parameters such as strain, temperature and pressure. FBG sensors have been reported to be effective in monitoring various environmental parameters, including temperature, strain, tilt, torsion, flow, humidity, chemicals, gas and structural health monitoring. However, reflective spectrum of FBG suffers from various noises and current traditional digital filter methods such as FIR and IIR filters will introduce phase distortions which are detrimental to Bragg wavelength detection requiring high precision. In this report, a Zero Phase Filter is proposed to detect Bragg wavelength of an unapodized uniform FBG embedded in a standard telecommunications single mode fibre optic cable. This report will compare phase distortion in terms of wavelength shifts in Bragg wavelength detection on both real and modified signals against current mainstream digital filters such as Butterworth Filter. Experimental results shows that the Zero Phase Filter is able to consistent achieve minimum or no phase distortion of approximately ±0.010 nm for both real and signals modified with various noise profiles and has the best performance among all digital filters tested. However, more improvements can be made to the Zero Phase Filter such as addition of low-pass Butterworth filters to reduce Gibbs phenomenon for more accurate readings. Nevertheless, Zero Phase Filters show promise for future biosensor development.